Production of Brown’s Gas using Hydroxy Generator - Venkata Ramesh Mamilla, Dr.; Sri Rama Murthy, K.; M.Vamsi Krishna, M.; S.S.S ManikanthaSwamy, T.; S.S.S ManikanthaSwamy, A.; Ramesh, A.; Uday Krishna, M. (International Journal of Engineering and Technology, 2018)
This paper deals with the designing of hydroxyl (HHO) generator and thus use the Brown’s Gas liberated from it as a supplement to increase fuel efficiency in IC engines.  The combustion process in IC engines is very primitive and hence unburnt fuel remains after the combustion process. This is a very challenging problem being faced by today’s automobile industry as this unburnt mixture is a serious air pollutant. The proposed approach is based on an ordinary HHO generator. Although people use HHO generators in practice a very little research has been carried out in implementing an efficient system. This project is mainly focused on finding an efficient configuration of an ordinary HHO generator that is efficient than an ordinary system. Here the generator was tested under several conditions in order to determine a convenient design for an efficient HHO generator.
Keywords: Production; Brown’s Gas; Hydroxy Generator